Intraneural Synovial Cyst of the Common Peroneal Nerve: An Unusual Cause of Foot Drop with Four-Year Follow-Up - Abrar Adil; Clint Basener; Jake Checketts (Case Reports in Orthopedics)
In our case report, we describe a 55-year-old male patient with isolated foot drop due to an intraneural synovial ganglion. We successfully treated the lesion with decompression via epineurotomy combined with primary division of the recurrent articular branch of the common peroneal nerve (CPN). Compression neuropathies of the common peroneal nerve arise from a variety of causes. Intrinsic compression due to intraneural ganglion cysts of the CPN is rare. Previous reports of simple decompression of the cystic fluid have resulted in recurrence. The unified articular theory describes a pathway for fluid to fill from the proximal tibiofibular joint into the CPN via a recurrent articular branch. In our case, we divide this articular branch which we feel prevents recurrence.